2015
DOI: 10.1590/s0004-28032015000100014
|View full text |Cite
|
Sign up to set email alerts
|

Cirrhosis Induces Apoptosis in Renal Tissue Through Intracellular Oxidative Stress

Abstract: -Background -Renal failure is a frequent and serious complication in patients with decompensated cirrhosis. ObjectiveWe aimed to evaluate the renal oxidative stress, cell damage and impaired cell function in animal model of cirrhosis. Methods -Secondary biliary cirrhosis was induced in rats by ligation of the common bile duct. We measured TBARS, ROS and mitochondrial membrane potential in kidney as markers of oxidative stress, and activities of the antioxidant enzymes. Relative cell viability was determined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…AKI is characterized by tubular cell injury and death (necrosis, apoptosis), which trigger endothelial activation and inflammatory cell recruitment . In an animal model, it has been reported that cirrhosis itself induces apoptosis in renal tissue by increase in intracellular reactive oxygen species and DNA damage . Therefore, it is quite possible that repeated minor insults to the kidney in a patient with cirrhosis, along with a chronic state of ongoing inflammation, causes reduction in GFR, leading to development of CKD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AKI is characterized by tubular cell injury and death (necrosis, apoptosis), which trigger endothelial activation and inflammatory cell recruitment . In an animal model, it has been reported that cirrhosis itself induces apoptosis in renal tissue by increase in intracellular reactive oxygen species and DNA damage . Therefore, it is quite possible that repeated minor insults to the kidney in a patient with cirrhosis, along with a chronic state of ongoing inflammation, causes reduction in GFR, leading to development of CKD.…”
Section: Discussionmentioning
confidence: 99%
“…(16) In an animal model, it has been reported that cirrhosis itself induces apoptosis in renal tissue by increase in intracellular reactive oxygen species and DNA damage. (17) Therefore, it is quite possible that repeated minor insults to the kidney in a patient with cirrhosis, along with a chronic state of ongoing inflammation, causes reduction in GFR, leading to development of CKD. These changes could accelerate in patients who have recurrent AKI or AKI that is severe and prolonged.…”
Section: Discussionmentioning
confidence: 99%
“…In this model, the characteristic features of the disease are established at approximately 28 d[10]. Studies have demonstrated that the changes occurring in cirrhosis in human patients are similar to those found in experimental models, including jaundice, hepatomegaly, splenomegaly, abnormal gas exchange, and oxidative damage[11-15]. …”
Section: Introductionmentioning
confidence: 99%
“…The resulting oxidative stress in the liver and kidney from the effect of ROS generation could have led to liver fibrosis and renal epithelial/endothelial injury, respectively [ 1 3 , 23 ]. Kidney might as well have been further affected by the generation of ROS due to the effect of subsequent liver fibrosis [ 24 ]. In addition to that, overloading of BSA might have aggravated the already mildly disrupted glomerular filtration barrier, which further aggravated the proteinuria.…”
Section: Discussionmentioning
confidence: 99%